Grading Evaluation of Goaf Stability Based on Entropy and Normal Cloud Model - Tianxing Ma; Yun Lin; Xiaobin Zhou; Mingzhi Zhang (Advances in Civil Engineering)
Aiming at the fuzziness and randomness of goaf stability classification, to obtain goaf stability classification more objectively, an entropy weight-normal cloud model for goaf stability classification is proposed. Based on the geological conditions and engineering conditions, 14 indexes that affect the stability of a goaf are selected to establish an evaluation index system, and the weight of each index is determined using the entropy weight method, which makes the weight distribution more objective. Based on the cloud model theory, the cloud numerical characteristics of each evaluation index belonging to goaf stability level are calculated, and a corresponding cloud model is generated. Combined with the entropy weight, the comprehensive certainty degree is calculated, and the evaluation results are obtained. Taking 25 mined-out areas in Xishan mine of Shandong Gold Mining and the Dabaoshan mine as examples, the model is used for stability evaluation, and the evaluation results are basically consistent with the actual situation, which proves the feasibility of the method and provides a new and effective method for stability evaluation of mined-out areas.